ANALISIS PENGARUH LUAS LAHAN PARKIR TERHADAP PENDAPATAN PEMILIK USAHA KAFE DAN RESTORAN DI KOTA BANDA ACEH - Dzaki Siraj; Fikriah Fikriah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to determine how the area of parking lots affects the income of cafe and restaurant business owners in Banda Aceh. The variables allegedly related to this research include a parking area, business location, number of customers, menus served, and will ultimately affect the income of cafe and restaurant business owners. The method used in this research is descriptive qualitative analysis method. This method is used to analyze measures of central bias, dispersion, and distribution of data, such as the average, median, variance, and maximum and minimum values. The data in this study used primary data obtained from the field through a questionnaire. Secondary data were obtained from data collection searches that can be accessed on books, journals, websites, and literature studies conducted in each respective agency. The results showed that the parking lot area influences the increasing number of visitors and an increase in cafe business revenue. Key Word: Parking, Revenue, Visitors, Cafe, Banda Aceh City